EFEKTIVITAS MIKROORGANISME LOKAL KULIT BUAH KAKAO DALAM MENGHAMBAT PERTUMBUHAN Colletotrichum acutatum J.H. Simmonds PADA TANAMAN CABAI MERAH (Capsicum annuum L.) - Salsabila, Salma; Yulianty, Yulianty; Wahyuningsih, Sri; Ernawiati, Eti (Fakultas Pertanian, Universitas Janabadra, 2024)
Colletotrichum acutatum is a pathogenic fungus in chili plants that causes anthracnose. The control of this disease usually involves the use of synthetic fungicides, but their long-term use may have negative impacts. One alternative to inhibit the growth of Colletotrichum acutatum is the use of natural fungicides, such as local microorganisms (LMOs) from cacao fruit skin. This study aims to determine the effectiveness of local microorganisms from cacao fruit skin in inhibiting the growth of Colletotrichum acutatum and to identify the best concentration of these local microorganisms in controlling Colletotrichum acutatum, the causative agent of anthracnose in red chili plants (Capsicum annuum L.). This study used a Completely Randomized Design (CRD) with 6 treatments, namely A (0 ml/l water), B (5 ml/l water), C (10 ml/l water), D (15 ml/l water), E (20 ml/l water), and F (25 ml/l water). Each treatment was repeated 4 times. The data were analyzed with variance analysis followed by an Honest Significant Difference (HSD) test at a level of 5% (α = 5%). The results of the study showed that local microorganisms from cacao fruit skin had a significant effect on the fungal colony diameter, germination percentage, plant height, disease occurrence, and disease severity. The best concentration of LMOs from cacao fruit skin was found in treatment F (25 ml/l water).